Learning outcomes and quality of educational service as predictors of academic satisfaction among Peruvian university students - Montesinos-Chávez, Marcela Candelaria; Pari-Rodríguez, Nelly Jaqaru; Jaime-Zavala, Milena Ketty; Jara-Herrera, Melva Rina; Andía-Gonzales, Brizaida Guadalupe; Duche-Pérez, Aleixandre Brian (Edelweiss Applied Science and Technology, 2025)
This study investigates the extent to which two learning outcome domains—personal and professional competencies, and digital competencies and social responsibility—and two educational service quality dimensions—teaching quality and academic resources/support—predict students’ academic satisfaction at a public university in Peru. A cross-sectional survey was administered to 734 undergraduate students aged 18–26 to assess these two learning outcome factors, two service quality factors, and overall satisfaction. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM) and ANOVA. The model was statistically significant (p < .001) and explained approximately 74% of the variance in student satisfaction. Among the predictors, academic resources/support emerged as the strongest, followed by personal/professional competencies and teaching quality. Digital competencies and social responsibility demonstrated a smaller but still significant positive effect. The findings suggest that student satisfaction is primarily driven by the quality of academic resources/support and effective teaching practices, along with robust personal/professional competencies. Conversely, digital competencies and social responsibility have a minor influence on satisfaction unless they are more fully integrated into the curriculum. To enhance student satisfaction, university management should focus on strengthening infrastructure and support services, improving teaching quality, embedding personal/professional competencies into the curriculum, and integrating digital competencies and social responsibility into authentic learning experiences.